Transitional labour markets in a transitional economy: Could they work? The example of Poland - Kamil Zawadzki (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2005)
The prospects for successful implementation of the TLM approach in Poland depend on numerous factors, and it is important to remember that the impact of these factors will rarely be one-dimensional. TLMs would entail a series of both advantages and disadvantages for employers, employees, the self-employed, non-paid workers, the unemployed, trainees and older workers facing retirement. Moreover, the unique mix of economic, social, technological and demographic changes found in Poland will have a substantial impact on the prospects for implementing TLMs. There is no conclusive answer to the question formulated in the title. A number of arguments suggest that the reply might be positive: the prospect of social and political approval for TLMs, EU membership, the need to combat widespread unemployment and illicit employment, the rising level of education, the high rate of economic growth, and many others. There are also, however, many potential obstacles: the poor level of agreement between the social partners, the lack of funds for ALMP, inadequate links between different employment statuses on the labour market, the scale of poverty, inadequate mobility, structural reforms, poor implementation of labour law, etc. – – Es gibt eine Vielzahl von Faktoren, die die Chancen einer effizienten Implementierung des Konzepts der Übergangsarbeitsmärkte (ÜAM) in Polen beeinflussen und die sich zudem selten in nur eine Richtung auswirken. ÜAM würden eine Reihe von Vor- wie Nachteilen für Arbeitgeber, Arbeitnehmer, Selbständige, Unbezahlte, Arbeitslose, Auszubildende und ältere Beschäftigte vor dem Ruhestand mit sich bringen. Darüber hinaus werden die Perspektiven für die Realisierung von ÜAM in Polen auch stark von den Besonderheiten des ökonomischen, gesellschaftlichen, technologischen und demographischen Wandels in diesem Lande bestimmt. Die im Titel formulierte Frage lässt sich nicht endgültig bejahen oder verneinen. Etliche Argumente sprechen für eine positive Antwort: die Aussicht auf gesellschaftliche und politische Zustimmung zu ÜAM, die EUMitgliedschaft, die Notwendigkeit, die hohe Arbeitslosigkeit und die weit verbreitete Schwarzarbeit zu bekämpfen, das steigende Bildungsniveau, das hohe Wirtschaftswachstum und vieles mehr. Es existieren jedoch auch viele potentielle Hindernisse: fehlendes Einvernehmen zwischen den Sozialpartnern, mangelnde finanzielle Mittel für aktive arbeitsmarktpolitische Maßnahmen, keine adäquaten Brücken für Übergänge in eine andere Erwerbsform, Armut, zu geringe Mobilität, Strukturreformen, schlechte Umsetzung des Arbeitsrechts usw.
Keywords: 330; Arbeitsmarktpolitik; Arbeitsmobilität; Übergangswirtschaft; Polen